Hydrothermal assisted sol–gel synthesis and multisite luminescent properties of anatase TiO2:Eu3+ nanorods. Issue 73 (9th August 2015) - Chang, Meiqi; Song, Yanhua; Zhang, Hongguang; Sheng, Ye; Zheng, Keyan; Zhou, Xiuqing; Zou, Haifeng
<x xml:space="preserve">Abstract</x> The relationship between local structure of Eu3+ ions and luminescence properties were discussed through site-selective spectroscopy at 10 K.